The intake of Kiwifruits improve the potential antioxidant capacity in male middle- and long-distance runners routinely exposed to oxidative stress in Japan - Imai, N.; Kobayashi, Y.; Uenishi, K. (Sports, 2021)
Oxidation damages cells and muscles, and thus, causes injuries and fatigue, which nega tively affect the conditioning of athletes. Thus, in this study, we aimed to investigate the effects of high-antioxidant fruits (kiwifruit) intake on oxidative stress level (d-ROMs) and antioxidant activity (BAP) in male middle- and long-distance runners routinely exposed to oxidative stress. This study was performed from May to July 2017 (Study 1) and October to December 2018 (Study 2). The subjects in Study 1 were 30 male runners, of which 15 consumed two yellow kiwifruits (Zespri® SunGold Kiwifruit) per day for one month of the survey period (Intake group). The subjects of Study 2 were 20 male runners who had high d-ROMs from preliminary testing. These runners consumed two yellow kiwifruits (Zespri® SunGold Kiwifruit) per day for two months. d-ROMs and BAP were measured using a free radical analyzer. In study 1, the d-ROMs decreased while the potential antioxidant capacity (BAP/d-ROMs ratio) increased in the Intake group. In study 2, BAP/d-ROMs ratio was higher after one and two months compared to that at pre-intervention. Study findings suggested that consumption of kiwifruits may reduce oxidative stress levels and increase antioxidant activity, resulting in improved potential antioxidant capacity.